Heart Transplantation in Muscular Dystrophy Patients: Is it a Viable Option?. (April 2020) - Wells, Dennis; Rizwan, Raheel; Jefferies, John L.; Bryant, Roosevelt; Ryan, Thomas D.; Lorts, Angela; Chin, Clifford; Zafar, Farhan; Morales, David L.
Abstract : Background: Cardiomyopathy is a common complication among muscular dystrophy (MD) patients and often results in advanced heart failure and premature death. In spite of this, there is hesitancy to consider heart transplantation (HTx). This study describes the HTx outcomes in patients with MD in the United States. Methods and Results: All HTx in the United Network for Organ Sharing database from October 1, 1987, to March 31, 2016, were identified. Two patient groups were created: MD cohort (n=81), and a cohort of all other cardiomyopathies, called cardiomyopathy-unmatched (n=41 317). Propensity score matching (ratio 1:2) was performed on transplant age, gender transplant year, renal function, and inotropic support at transplant to form a cardiomyopathy-matched cohort (n=162). Patient characteristics and posttransplant outcomes were compared. In the 81 patients with MD, Becker was the most common type (42%–52%). All the analyzed preoperative characteristics did not statistically differ between the MD and cardiomyopathy-matched cohorts except ventricular assist device use (16% versus 30%; P =0.017), ventilator support (0% versus 6%; P =0.031), and donor race mismatch (30% versus 55%; P <0.001). Median time on waitlist was not statistically different between the 2 groups (52 versus 59 days; P =0.12). Posttransplant survival of MD cohort was not statistically different compared with cardiomyopathy-matched cohort ( P =0.18; hazard ratio [95% CI], 0.71 [0.42–1.18]) and was better than the cardiomyopathy-unmatched cohort ( P =0.004; hazard ratio [95% CI], 0.53 [0.34–0.82]). Among the types of MD, no statistical difference was observed in posttransplant survival of Becker MD versus non-Becker MD ( P =0.12; hazard ratio [95% CI], 2.17 [0.79–6.01]). Conclusions: Patients with MD undergoing HTx had similar long-term posttransplant survival compared with matched cardiomyopathy-related HTx recipients. HTx appears to be an effective treatment for a select group of muscular dystrophy patients with end-stage heart failure.